2007
DOI: 10.1038/sj.ejcn.1602966
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in the relationship between mid-upper arm circumference and maximum voluntary contraction among ethiopian farmers

Abstract: Objectives: To determine the nature of the relationship between mid-upper arm circumference (MUAC) and maximum voluntary contraction (MVC) in pre-and post-harvest seasons among adult Ethiopian farmers. Subjects/Methods: A total of 491 healthy adult men aged 18-60 years were recruited at pre-harvest season and followed up at post-harvest season. Anthropometric measurements (weight, MUAC, biceps/triceps skinfold thickness and forearm circumference) were obtained using standard techniques and arm muscle circumfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Investigations on upper extremities or lower extremities through ultrasound detection have proposed relationships between muscle thickness and torque, which is the representation of the contractile force [7,16,23]. Several published papers correlated limb circumference with torque [26,28,34] without elaborating its underlying mechanism. Accordingly, the muscle thickness can be an index for muscle contraction, while muscle volume seldom changes during contraction [35].…”
Section: Hypothesis and Structural Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Investigations on upper extremities or lower extremities through ultrasound detection have proposed relationships between muscle thickness and torque, which is the representation of the contractile force [7,16,23]. Several published papers correlated limb circumference with torque [26,28,34] without elaborating its underlying mechanism. Accordingly, the muscle thickness can be an index for muscle contraction, while muscle volume seldom changes during contraction [35].…”
Section: Hypothesis and Structural Designmentioning
confidence: 99%
“…Investigations on the upper extremities or lower extremities through ultrasound detection have proposed relationships between muscle thickness and torque, which is the representation of the contractile force [7,16,23]. Several published papers correlated LC with torque [26,28,34] without elaborating its underlying mechanism.…”
Section: Hypothesis and Structural Designmentioning
confidence: 99%
See 1 more Smart Citation
“…AMA exhibited higher coefficients of determination (r 2 adjusted ) than BMI, as was verified in the study by Barbosa et al 6 and by Pieterse et al 7 , with the elderly of Ruanda, living in refugee camps in Tanzania. This finding can be justified by a closer relationship between the AMA measure and muscle mass in the elderly 23 . Studies carried out in developed countries have shown conflicting results in relation to this issue.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 88%
“…The link between MVC, muscle strength and circumference has already been established [1] [12]. Our research is about trying to establish an easy to obtain sensor position, such that automatic circumference measurements might be able to estimate MVC for automatic calibration within an acceptable error.…”
Section: Discussionmentioning
confidence: 99%